Interiorizatsionnye aspekty ekstremal'nykh situatsii sorevnovatel'nogo kharaktera - Gogunov, E. N. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The purpose of this paper was to form the interiorizational theory for the overcoming of extreme situations in professional activity. The technique of research: the study and analysis of the references on the theme, the pedagogical experiment. The objects of the research: athletes (archery), students, cadets. Results: the steady and the authentic reduction of the extremeness difficulty parameters of competitive character under the condition of the purposeful training of athletes for their overcoming; the temporary period of acceptance of the decision in extreme conditions 34,97% reduction; the level of emotional excitation at the occurrence of extreme situations 3,47% reduction; the productivity of actions in extreme conditions 9,4% increasing.